Formation of an organisational and technological mechanism to improve the manufacturability of works in total building renovation - Rima S. Petrosyan (Stroitel’stvo: Nauka i Obrazovanie, 2023)
Introduction. Modern methods of executing total building renovation are based on the principles of flow and scientific methods of labour organisation, developed with due regard for the specific features of certain types of repair and construction works technologies. The following labour-intensiveness and duration of work, material-intensiveness, cost and production cost of constructions are considered as the main indicators of work production technology in the course of overhaul repair. Each of these indicators has corresponding reserves, which are identified and used to improve the manufacturability of production of each type of work, as well as on the building as a whole.Materials and methods. The article is based on the method of assessing the effectiveness of various options to reduce the duration of work, which directly affects the change in technological parameters. A ranking among contractors has been carried out to identify the reserves for increasing labour productivity, as well as to identify bona fide contractors for customers.Results. The developed methodology of evaluation of manufacturability of overhaul works allows contractors to justify for customers the proposals on reduction of terms and cost of overhaul works. The use of the developed organizational and technological mechanism in practice of interaction of all participants of capital repair process will allow not only to achieve the highest indicators, but also will serve as a basis for actualization of normative documents on total building renovation.Conclusions. The method of efficiency estimation of different variants of work time reduction and related changes of technological parameters according to Wald, Savage and Hurwitz criteria allowed to establish the most preferable construction-technological solution. The developed rating assessment of contractors will, on the basis of achieved results, enable to reveal reserves of increasing labour productivity in the course of repair-construction works and to encourage these organizations to be more preferable in carrying out competitive procedures of selecting contractors by the customer. The identified reserves of reducing the duration of overhaul works are used as a basis for the formation of measures to improve the manufacturability of works.